2020
DOI: 10.3390/nu12040907
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Replacement Improves High-Fat Diet-Induced Obesity by Suppressing the Action of Ghrelin in Ovariectomized Rats

Abstract: This study aims to investigate the effects of estradiol replacement on the orexigenic action of ghrelin in ovariectomized (OVX) obese rats fed with a high-fat diet (HFD). Four weeks after OVX at 9 weeks of age, Wistar rats were subcutaneously implanted with either 17β-estradiol (E2) or placebo (Pla) pellets and started on HFD feeding. After 4 weeks, growth hormone-releasing peptide (GHRP)-6, a growth hormone secretagogue receptor (GHSR) agonist injected intraperitoneally, induced changes in HFD intake, and c-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
1
14
0
3
Order By: Relevance
“…In this study, E2 replacement suppressed the increase in energy intake and body weight in HFD‐fed OVX rats more strongly than in NCD‐fed rats, as already shown in our previous report (Yokota‐Nakagi et al, 2020). Contrarily, a previous study reported that food intake was slightly lower in OVX mice than E2‐replaced mice fed on HFD, despite being more obese (Camporez et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, E2 replacement suppressed the increase in energy intake and body weight in HFD‐fed OVX rats more strongly than in NCD‐fed rats, as already shown in our previous report (Yokota‐Nakagi et al, 2020). Contrarily, a previous study reported that food intake was slightly lower in OVX mice than E2‐replaced mice fed on HFD, despite being more obese (Camporez et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Protein levels from the liver and muscles were analyzed by western blotting according to previously published protocols (Kawakami et al, 2018; Yokota‐Nakagi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As E 2 treatment has previously been shown to reduce OVX-induced weight gain in both mice (Couse and Couse and Korach, 1999 ; Litwak et al, 2014 ) and rats ( Hertrampf et al, 2006 ; Sibonga et al, 1998 ; Wegorzewska et al, 2008 ), it was surprising that E 2 -treated mice did not exhibit significantly lower body weights than vehicle-treated mice. This lack of effect may be at least partially mediated by our use of a standard diet instead of a high-fat diet, as supported by previous rat ( Weigt et al, 2012 ; Yokota-Nakagi et al, 2020 ) and mouse studies ( Litwak et al, 2014 ). It is not surprising, however, to find that neither DPN nor EGX358 reduced weight gain compared to vehicle, as previous studies report mixed results, such that either no effect of phytoestrogen diets or ERβ agonist treatment was observed in rats ( Hertrampf et al, 2007 , 2008 ; Weigt et al, 2012 ), positive effects were found only under high-fat diet conditions in wild-type compared to ERβ knockout mice ( Foryst-Ludwig et al, 2008 ), or negative effects were shown under standard diet conditions in mice ( Said et al, 2018 ).…”
Section: Discussionmentioning
confidence: 62%
“…As ovarian function declines, estrogen production and estrogen receptor function also decline, leading to abdominal fat accumulation and metabolic abnormalities in menopausal women [ 1 ]. Estrogen plays an important role in controlling food intake and body weight [ 2 ].…”
Section: Introductionmentioning
confidence: 99%